Effect of carrier materials on the properties of the andrographolide solid dispersion - Shoude Zhang; Qingyun Zeng; Guowei Zhao; Wei Dong; Liquan Ou; Ping Cai; Zhenggen Liao; Xinli Liang (Universidade de São Paulo, 2022)
Abstract In the work the andrographolide (AG)-solid dispersions (SDs) were prepared by the spray-drying method, using polyethylene glycol 8000 (PEG8000), Poloxamer188, polyvinylpyrrolidone K30 (PVPK30), Soluplus® as carrier materials. The effect of different polymers as carrier materials on the properties of the AG-SDs were studied. The results showed obvious differences in intermolecular interaction, thermal stability, drug state, powder properties, dissolution behavior, and so on of AG-SDs prepared using different polymers as carrier materials. AG-PEG8000-SD was a partial-crystalline and partial-amorphous powder with smaller surface area and pore volume, but it was easy to wetting and did not swell in contact with dissolved medium. AG-Soluplus®-SD was completely amorphous powder with larger specific surface area and pore volume, but it swelled in contact with water. Therefore, the dissolution profile of AG in AG-PEG8000-SD was similar to that in AG-Soluplus®-SD. Soluplus® and PEG8000 were suitable polymers to design AG-SDs, considering both physicochemical properties and dissolution behaviors. The results of this reseach showed that when selecting carrier materials for SD, we should not only consider the state of drugs in SD and the powder properties of SD, but also consider whether there is swelling when the carrier materials are in contact with the dissolution medium.